5.2k views
3 votes
(1−cos^2 x )·(1+tan^2 x)

1 Answer

5 votes

Answer:


(1-cos^2 x ).(1+tan^2 x) = tan^2x

Explanation:

Given


(1-cos^2 x ).(1+tan^2 x)

Required

Solve


(1-cos^2 x ).(1+tan^2 x)

In trigonometry;


1 - cos^2x = sin^2x

So, make substitution


(1-cos^2 x ).(1+tan^2 x) becomes


(1-cos^2 x ).(1+tan^2 x) = (sin^2 x ).(1+tan^2 x)

Also; in trigonometry:


1 + tan^2x = sec^2x

Make another substitution


(1-cos^2 x ).(1+tan^2 x) = (sin^2 x ).(sec^2 x)

Recall that
secx = (1)/(cosx)

So;


(1-cos^2 x ).(1+tan^2 x) = (sin^2 x ).(sec^2 x) becomes


(1-cos^2 x ).(1+tan^2 x) = (sin^2 x ).((1)/(cos^2 x))


(1-cos^2 x ).(1+tan^2 x) = (sin^2 x )/(cos^2 x)


(1-cos^2 x ).(1+tan^2 x) = ((sin x )/(cosx))^2

In trigonometry;


tan x = (sin x)/(cos x)


(1-cos^2 x ).(1+tan^2 x) = tan^2x

The expression cannot be further simplified

User Greg Kaleka
by
5.1k points